ANALISIS KEBUTUHAN KONDISI FISIK PEMAIN TENIS MEJA - andriani, sonya ayu (Jurnal Kesehatan Olahraga, 2019)
Physical condition is a whole unit of components that cannot be separated, increased, and maintained. In the game of table tennis requires a complete physical condition in order to support better performance. The purpose of this study was to determine the component requirements of physical conditions in table tennis players. This research uses descriptive quantitative research using the formula mean and percentage. The subjects in this study were world players Ma Long and Fanzhendong in the men's singles match the World Table Tennis Championships 2017 Men's singles final in Germany.Components of general physical conditions include: strength, endurance, explosive power, speed, flexibility, balance, coordination, accuracy and reaction. The results of this study can be seen the needs of the physical condition of table tennis in the game as a whole. The results of the research obtained are as follows: the components of physical conditions needed are muscleendurance anaerobic, arm muscle power, reaction time, agility and coordination. The most frequently used technique can be seen from the results of the following percentages: spin 54,792%, chop 20,976%, block 13,200%, flick 9,041%, drive 1,084%, and smash 0,904%. Conclusion in the table tennis game physical components needed are muscleendurance anaerobic, arm muscle power, reaction time, agility and coordination. Keywords : Table Tennis, Physical Condition